AVIPTADIL; Class effect of a Synthetic VIP as a treatment option in COVID 19 patients with severe respiratory failure - Dwaipayan Sarathi Chakraborty; Shouvik Choudhury; Sandeep Lahiry (Medicine Science, 2022)
Despite dynamic drug and vaccine developmental processes to reduce the disease burden of COVID 19, still the options for treatment are very limited. Vasoactive peptide (VIP) has diversified physiological action with specific features of lung protection-related activities. VIP inhibits SARS COV-2 gene replication in human monocytes and viral replication in Calu -3 cells thus further reducing the generation of proinflammatory mediators Aviptadil, a synthetic form of VIP, is the only pulmonary therapeutic agent to have been granted Fast Track status by the US FDA and to be allowed into both phase 2/3 clinical trials Initial binding of Aviptadil with nsp10 & nsp 16 which may inhibit the 2 -O-MTase activity of the SARS-CoV nsp10/16 complex Aviptadil as a synthetic VIP has already been proved to be an effective option in the treatment of severe respiratory failures due to sepsis and other related lung injuries. Interim analysis results of this drug use in respiratory failures caused by SARS COV-2 has evolved a new hope in regards to safety and efficacy. Final results from recently completed as well as all currently ongoing trials will clarify the class effect of this drug in the treatment of COVID 19 in future days. [Med-Science 2022; 11(1.000): 433-8]